Legal Regulation of Electric Vehicles in Indonesia: Challenges and Directions of National Policy - Gugat, Rudy Max Damara; Nugroho, Aditya; Fadhil, Dimas Nu'man (PT. Anagata Sembagi Education, 2025)
The global energy paradigm shift is driving the transformation of the transportation sector, where electric vehicles are seen as a strategic solution to reduce dependence on fossil fuels and reduce carbon emissions. Indonesia, through its commitment to net zero emissions 2060, has responded to this issue by issuing key regulations, namely Presidential Regulation 55 of 2019 and Presidential Regulation 79 of 2023. Presidential Decree 79/2023 expands the scope of policies, not only focusing on accelerating the adoption of electric vehicles, but also emphasizing industrialization, supply chain development, fiscal incentives, and infrastructure acceleration. However, this regulation is not yet fully in sync with Law 22 of 2009 concerning Road Traffic and Transportation, which is still oriented towards fossil fuel vehicles. This condition creates a regulatory gap in the aspects of type tests, safety standards, and battery waste management. Therefore, regulatory harmonization is absolutely necessary so that electric vehicles can operate legally, safely, and sustainably. This study uses a normative juridical method with a legislative, conceptual, and comparative approach, to examine the integration of Presidential Regulation 79/2023 with Law 22/2009. The analysis was carried out in a descriptive-analytical manner to find strengths, weaknesses, and needs for regulatory reform. The results of the research are expected to make a real contribution to the direction of national legal policies that are consistent, adaptive, and support the sustainable energy transition in Indonesia.